Experimental Study on Gas Slippage of Tight Gas Sands in Kirthar Fold Belt Sindh, Pakistan - Mahesar, Aftab Ahmed; Shar, Abdul Majeed; Memon, Khalil Rehman; Rehman, Hafeez-ur-; Baladi, Shahzad Ali (Mehran University Research Journal of Engineering and Technology; Vol 36 No 3 (2017): July Issue, 2017)
The laboratory experiments on samples from Kirthar fold belt of lower Indus basin Sindh Pakistan were carried out to investigate the effect of gas slippage under varying conditions of pore pressures and overburden stress. The samples were dried in an oven at temperature of 600C and were randomly selected for measurement of permeability and porosity. Permeability was measured using nitrogen gas, while the porosity measurements were made using helium gas expansion porosimeter. The bulk volume was determined by measuring sample diameter and length with caliper. The permeability results suggest that gas slippage increases as if low pore pressures are used, which leads to higher measured permeability than intrinsic permeability of samples. An attempt was also made to estimate the permeability using existing correlations and found that there is large scatter in predicted permeability and measured data. This large amount of scatter in the predicted permeability values concludes that unless absolutely necessary, such correlations should not be used where accurate absolute permeability values are needed. Moreover, the permeability and porosity were plotted together to develop a relation between two properties; the power law fitting of the data well explains the relation between permeability and effective porosity.